HUBUNGAN DISFAGIA DAN PENURUNAN KESADARAN TERHADAP PNEUMONIA ASPIRASI PADA PASIEN STROKE RS ATMA JAYA - Michael Nathaniel Budiarso,* Linda Suryakusuma,** Luse,*** Vetinly**** (Neurona Majalah Kedokteran Neuro Sains, 2018)
INTRODUCTION APPROXIMATELY 4096 OF STROKE PATIENTS WILL DEVELOP COMPLICATIONS THE MOST FREQUENT IS PNEUMONIA 33 THIS IS DUE TO THE UNDERLYING CLINICAL MANIFESTATION OF STROKE SUCH AS DYSPHAGIA IMMOBILIZATION ALTERED LEVEL OF CONSCIOUSNESS AND IMMUNE SUPPRESSION WHICH INCREASES THE RISK OF ASPIRATION THEREFORE INCREASES THE RISK FOR ASPIRATION PNEUMONIA EARLY DETECTION OF ASPIRATION PNEUMONIA AND ITS RISK FACTORS IN STROKE PATIENTS ARE ESSENTIAL BUT THE NUMBER OF RESEARCHES REGARDING THIS IN INDONESIA IS STILL LIMITED